KLAUSA PEMBANDINGAN DALAM KALIMAT MAJEMUK BERTINGKAT BAHASA INDONESIA - Winda Kartika; Mukhlish Mukhlish (CARAKA, 2016)
The purposes of this research are to describe the comparing conjunction, the nature of the appearance of the conjunction in comparing clause, the position and the structure of the comparing clause, and the disengagement of syntax function in comparing clause in Indonesian compound-complex sentence. This research is a descriptive qualitative research. The data of this research are the compound-complex sentences containing comparing clause. The sources of the data are written ones including those from the daily newspaper, magazines, literature works, and books. The presentation data method is the â€œsimakâ€ method with â€œsimak bebas libas cakapâ€ and note-taking techniques. The data were analyzed using â€œagihâ€ methode with â€œbagi unsur langsungâ€ technique, followed by â€œgantiâ€, â€œbalikâ€, â€œbaca markahâ€, and â€œlesapâ€ techniques. The presentation methods of the data analysis were done using the informal and informal method. The results of this research are (1) The conjunction in comparing clause in Indonesian compound complex sentence including (a) seperti, (b) bagai(-kan), (c) ibarat, (d) seakan(- akan), (e) seolah(-olah), (f) serasa(-rasa), (g) sebagaimana, (h) laksana, (i) daripada, (j) alih-alih, (k) sebagai, dan (l) bak. (2) The nature of the appearance of the conjunction in Indonesian compound complex sentence is obligatory. (3) The position of comparing clause in a compound complex sentence has the concession of placement. (4). The comparing clause in Indonesian compound complex sentence has the annotation with the structure of Conj Pb+(S)+P+(O)+(Comp)+(Adv).Â  This Â structureÂ  includes Â (a)Â  Conj Â Pb+S+P, Â (b) Conj Pb+(S)+P, (c) Conj Pb+S+P+O, (d) Conj Pb+(S)+P+O, (e) Conj Pb+S+P+Com, (f) Conj Pb+(S)+P+Comp, (g) Conj Pb+S+P+Adv, (h) Conj Pb+(S)+P+Adv, (i) Conj Pb+S+P+O+Adv, dan (j) Konj Pb+S+P+Comp+Adv. (5) The disengagement of syntax function in comparing clause is in the form of the disengagement of the subject. This can be done when the core clause and comparing clause are conferential.